2000
DOI: 10.1074/jbc.275.14.9901
|View full text |Cite
|
Sign up to set email alerts
|

IHG-2, a Mesangial Cell Gene Induced by High Glucose, Is Human gremlin

Abstract: We used cloning in silico coupled with polymerase chain reaction to demonstrate that IHG-2 is part of the 3-untranslated region of gremlin, a member of the DAN family of secreted proteins that antagonize the bioactivities of members of the transforming growth factor (TGF)-␤ superfamily. Mesangial cell gremlin mRNA levels were induced by high glucose, cyclic mechanical strain, and TGF-␤1 in vitro, and gremlin mRNA levels were elevated in the renal cortex of rats with streptozotocin-induced diabetic nephropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 20 publications
1
65
1
1
Order By: Relevance
“…We have previously demonstrated that the anti-proliferative effects of LXA 4 are mediated through activation of the ALXR and result in modulation of growth factor (PDGF and EGF) receptor phosphorylation leading to down-regulation of the PI 3-kinase signaling pathway (4,9,18). Here, we report that the ability of LXA 4 to reduce the tyrosine phosphorylation level of the PDGFR␤ is independent of inhibition of RTK activity but dependent on SHP-2 PTP activation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We have previously demonstrated that the anti-proliferative effects of LXA 4 are mediated through activation of the ALXR and result in modulation of growth factor (PDGF and EGF) receptor phosphorylation leading to down-regulation of the PI 3-kinase signaling pathway (4,9,18). Here, we report that the ability of LXA 4 to reduce the tyrosine phosphorylation level of the PDGFR␤ is independent of inhibition of RTK activity but dependent on SHP-2 PTP activation.…”
Section: Discussionmentioning
confidence: 54%
“…These data suggest that the high affinity binding site for the recruitment of p85 (Tyr 751 ) is the site most likely to be modulated by LXA 4 , although both sites must be mutated before a complete block in the effect of LXA 4 is observed. These data are particularly noteworthy given that p85 is a component of the PI 3-kinase complex, and our previous data have demonstrated that LXA 4 inhibits MC PI 3-kinase activity in response to leukotriene D 4 and PDGF, respectively (4,18). Consistent with our observations in ALXR cells expressing the Y740F/Y751F mutant, PDGF-induced phosphorylation of Tyr 751 was significantly inhibited by preincubation with LXA 4 in primary MC as assessed by immunoblot analysis using an antibody specific against PDGFR␤-Y751 phosphorylation (supplemental data).…”
Section: Resultsmentioning
confidence: 91%
“…Hence, there is a need for the development of other agents to be used in conjunction with insulin treatment to help prevent diabetes-related complications such as diabetic nephropathy. Figure 8 indicates how TGF-␤ production and its subsequent effect on albumin uptake by proximal tubule cells may be influenced by glucose (8), glycated albumin (43), AngII (44), and changes in TGF-␤-regulating proteins such as decreased BMP7 (14) and increased gremlin (45), a protein that decreases BMP7 production (46). High glucose may also influence albumin uptake by proximal tubule cells, which may or may not act via a TGF-␤-related mechanism (47).…”
Section: Discussionmentioning
confidence: 99%
“…This compares with blood glucose levels in age-matched control animals of between 50 and 80 mg/dl. RNA was extracted from the kidney cortex as described previously (9). With respect to the remnant kidney model, male Munich-Wistar rats (260 -290 g) underwent 5/6 nephrectomy as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…The role of ROS on actin cytoskeleton regulatory protein mRNA levels in response to high glucose was investigated by culturing mesangial cells in either 30 mM glucose or 30 mM glucose with carbonyl cyanide m-chlorophenylhydrazone (CCCP) (Sigma) (0.5 M), an uncoupler of oxidative phosphorylation, for 7 days (7). To investigate the role of cyclical stretch, cells cultured on flexible plates were subjected to repeated cycles of computer-controlled, vacuum-driven mechanical stretch and relaxation using the Flexercell Strain Unit (Flex Cell International, Hillsborough, NH) as described previously (9).…”
Section: Methodsmentioning
confidence: 99%